Permeabilidade a água e germinação de sementes heteromórficas de Bowdichia virgilioides Kunth - Silva, Raquel Gonçalves [UNESP] (2015)
It's not particularity of Bowdichia virgilioides Kunth to show seeds with variations in tone of the integument, but for this specie, the gradient between light and dark tones is directly related to the absorption capacity of water of the seeds. The relationship between integument coloration with the permeability of the seeds of the species and the impacts on capacity, time and sync germination is one of the research objectives. Another objective was to relate the color with the formation of seedlings from seeds that undergone pre-germination treatments were the research objectives. Seeds collected between 2009 and 2011 formed five samples with yellow / orange integument (A1), orange (A2), orange / reddish (A3), reddish (A4) and red-rustiness (A5). Three years after the last collection, previously soaked in 20 seeds moistened paper and incubated at 25°C were individually weighed every 1 or 2 hours up to 7 days. In addition to this, two experiments independent of germination were conducted under continuous fluorescent white light at 25ºC with four replications of 25 seeds in a randomized design, evaluating the protrusion of radicle for 65 days and the formation of seedlings every 7 days for 49 days. In the first experiment, the treatments were the samples A1, A2, A3, A4, A5 and the second were formed by the factorial 5 x 2 (x samples pre-germination treatments: chemical and thermal). The gradient between yellowish / Orange to red integuments occurred rustiness increases in water absorption, being more pronounced as the degree of darkening. The mortality rates of over 40%, mainly seeds with red-ferrugíneo husk, reduced seed germination reaching only 55%. The late germination estimated at approximately 20 days to the beginning to 55 days for the end, the intervals of 2 to 3 days with no occurrence of germination and the low synchrony characterized the germination of species as irregular and ...